IDENTIFICATION OF MYCOHETEROTROPHIC PLANTS (Burmanniaceae, Orchidaceae, Polygalaceae, Tiuridaceae) IN NORTH SUMATRA, INDONESIA - Dina Handayani; Salwa Rezeqi; Wina Dyah Puspita Sari; Yusran Efendi Ritonga; Hary Prakasa (Universitas Negeri Medan, 2020)
The majority of mycoheterotrophic herbs live in shady and humid forest. Therefore, the types of mycoheterotrophic plant are very abundant in tropical areas. One of the areas in Indonesia with the tropics is North Sumatera province. Unfortunately, the information about the species of mycoheterotrophic in North Sumatra is still limited. The objective of the research was to figure out the types of mycoheterotrophic plants in North Sumatra. The study was conducted in August until October 2019 in several areas of the Natural Resources Conservation Hall (BBKSDA) of North Sumatra province, the nature Reserve and nature Park. The research sites covered Tinggi Raja Nature Reserve, Dolok Sibual-Buali Nature Reserve, Sibolangit Tourist Park and Sicike-Cike Natural Park. In conducting sampling, the method used was through exploration or cruising method. The list of mycoheterotrophic plant species presented in this study consisted of their scientific names, synonyms, descriptions, distributions, and ecological information. A total of 9 species of mycoheterotrophic plants (4 families) in Sumatra have been found. As for the family Burmanniaceae, there are three species Burmannia championii, Burmannia lutescens, Gymnosiphon aphyllus. On the other hand, as for the Orchidaceae, there are 4 species, such as Didymoplexis pallens, Eulophia zollingeri, Galeola lindleyana, Gastrodia verrucosa while for the Poligalaceae and Tiuridaceae family, simply one type is found: Epirixanthes elongata and Sciaphila Secundiflora, respectively.